MARKETING POLITIK CALON KEPALA DESA DI DESA MARINDAL 1 KABUPATEN DELI SERDANG - Khairunnisah Lubis; Khairullah Khairullah (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
This study aims to explore the concept of political marketing applied by village head candidates in village head elections. The location of this study is in the village of Marindal 1, Deli Serdang district. This paper uses a descriptive method in presenting data and conducting analysis. The results of this study found that village head candidates generally carried out the concept of political marketing, but the personality factor and the effectiveness of the political marketing concept became dominant in achieving a succession of wins in village head elections.